2019
DOI: 10.1002/hpm.2846
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration for drug prevention: Is it possible in a “siloed” governmental structure?

Abstract: Summary Purpose Norwegian municipalities report that drug misuse is the most important public health challenge. The municipalities play a unique role in drug prevention aimed at youth, since young people rely on several services in their daily lives that are organized by different municipal departments. However, the municipal structure is described as siloed, and the policy areas as differentiated. This situation has led to a need for integration between different policy sectors to prevent drug use and promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…For instance, Williams et al ( 2023) not only argued that an intersectional lens should be applied in urban planning for health equity, but also outlined four strategies for accomplishing this: challenging assumptions, fostering cross-sectoral collaboration, co-designing strategies, and looking to established tools and resources. 62 Also, in a case study of a Norwegian city, Oldeide et al 63 identified siloing as one of the biggest hurdles to successfully managing youth drug prevention. Siloing often created confusion regarding the jurisdictional ownership of drug prevention mandates, resulting in uncertainty over which departments are and are not responsible for addressing youth drug prevention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Williams et al ( 2023) not only argued that an intersectional lens should be applied in urban planning for health equity, but also outlined four strategies for accomplishing this: challenging assumptions, fostering cross-sectoral collaboration, co-designing strategies, and looking to established tools and resources. 62 Also, in a case study of a Norwegian city, Oldeide et al 63 identified siloing as one of the biggest hurdles to successfully managing youth drug prevention. Siloing often created confusion regarding the jurisdictional ownership of drug prevention mandates, resulting in uncertainty over which departments are and are not responsible for addressing youth drug prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Siloing often created confusion regarding the jurisdictional ownership of drug prevention mandates, resulting in uncertainty over which departments are and are not responsible for addressing youth drug prevention. 63 This was exacerbated by the lack of meaningful opportunities for cross-sectoral collaboration, preventing policy-makers from different departments from effectively pooling together their knowledge and resources. 63 Lowe et al (2022) similarly acknowledged the limitations posed by siloing in municipal policy-and decision-making, stating that the creation of healthy and sustainable cities could not occur without integrated urban planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This perceived lack of collaboration may potentially lead to fragmented services as a result of an unclear mandate for collaboration throughout the municipal organisation. Previous research has highlighted the importance of advisers receiving a clear mandate to collaborate in order to effectively address drug prevention in a siloed governmental structure (Oldeide, Fosse, & Holsen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research literature on local health promotion and collaboration has been devoted to describing how municipalities face the challenges associated with intersectoral collaboration [10][11][12][13][14]. Previous research has demonstrated that the sports sector has successfully been used as a tool for promoting health through reaching vulnerable groups, creating social inclusion, integrating refugees, preventing crime, and addressing other complex public health challenges [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%